Global minimally invasive pyeloplasty study in children: Results from the Pediatric Urology Expert Group of the European Association of Urology Young Academic Urologists working party. Issue 4 (August 2016) - Silay, M.S.; Spinoit, A.F.; Undre, S.; Fiala, V.; Tandogdu, Z.; Garmanova, T.; Guttilla, A.; Sancaktutar, A.A.; Haid, B.; Waldert, M.; Goyal, A.; Serefoglu, E.C.; et al.
Summary: Introduction: Minimally invasive pyeloplasty (MIP) for ureteropelvic junction (UPJ) obstruction in children has gained popularity over the past decade as an alternative to open surgery. The present study aimed to identify the factors affecting complication rates of MIP in children, and to compare the outcomes of laparoscopic (LP) and robotic-assisted laparoscopic pyeloplasty (RALP). Materials and methods: The perioperative data of 783 pediatric patients (<18 years old) from 15 academic centers who underwent either LP or RALP with an Anderson Hynes dismembered pyeloplasty technique were retrospectively evaluated. Redo cases and patients with anatomic renal abnormalities were excluded. Demographics and operative data, including procedural factors, were collected. Complications were classified according to the Satava and modified Clavien systems. Failure was defined as any of the following: obstructive parameters on diuretic renal scintigraphy, decline in renal function, progressive hydronephrosis, or symptom relapse. Univariate and multivariate analysis were applied to identify factors affecting the complication rates. All parameters were compared between LP and RALP. Results: A total of 575 children met the inclusion criteria. Laparoscopy, increased operative time, prolonged hospital stay, ureteral stenting technique, and time required for stenting were factors influencing complication rates on univariate analysis. None of those factors remained significant on multivariate analysis. Mean follow-up was 12.8 ± 9.8 months for RALP and 45.2 ± 33.8 months for LP ( P = 0.001). Hospital stay and time for stenting were shorter for robotic pyeloplasty ( P < 0.05 for both). Success rates were similar between RALP and LP (99.5% vs 97.3%, P = 0.11). The intraoperative complication rate was comparable between RALP and LP (3.8% vs 7.4%, P = 0.06). However, the postoperative complication rate was significantly higher in the LP group (3.2% for RALP and 7.7% for LP, P = 0.02). All complications were of no greater severity than Satava Grade IIa and Clavien Grade IIIb. Discussion: This was the largest multicenter series of LP and RALP in the pediatric population. Limitations of the study included the retrospective design and lack of surgical experience as a confounder. Conclusions: Both minimally invasive approaches that were studied were safe and highly effective in treating UPJ obstruction in children in many centers globally. However, shorter hospitalization time and lower postoperative complication rates with RALP were noted. The aims of the study were met.